1977
DOI: 10.1111/j.1751-1097.1977.tb07425.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOSYNTHETIC ACTION SPECTRA AND LIGHT‐HARVESTING IN GRIFFITHSIA MONILIS (RHODOPHYTA)

Abstract: In cells of the red alga Grifithsia monilis the action spectrum of photosynthetic oxygen production at low light intensity shows that the phycobilins (including allophycocyanin) are the major light-harvesting pigments. As the light intensity is increased carotenoids and chlorophyll a contribute proportionately more to the spectrum, since the phycobilin activity becomes light-saturated. When action spectra are performed against a background light of various monochromatic wavelengths it can be shown that chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In the red alga Griffithsia monilis Harvey the phycobilins are the major light-harvesting pigments under low light intensities, whereas with increasing photon flux density, carotenoids and chlorophyll a contribute proportionally more {Larkum & Weyrauch, 1977). B. radicans is very likely to respond in a similar manner as G. monilis.…”
Section: Discussionmentioning
confidence: 89%
“…In the red alga Griffithsia monilis Harvey the phycobilins are the major light-harvesting pigments under low light intensities, whereas with increasing photon flux density, carotenoids and chlorophyll a contribute proportionally more {Larkum & Weyrauch, 1977). B. radicans is very likely to respond in a similar manner as G. monilis.…”
Section: Discussionmentioning
confidence: 89%
“…Hence, a possible importance of light quality for red algal growth at very low levels was missed. The fading importance of phycobilins at increasing light intensity had been stressed by Larkum & Weyrauch (1977). These authors had found from photosynthetic action spectra in the red alga Griffithsia monilis that at low intensity the phycobilins are the major light-harvesting pigments, while at increasing light intensity chlorophyll and carotenoids contribute proportionately more to the spectrum since the phycobilin activity becomes light-saturated.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the available light over the vertical profile studied here in spring did not cause changes in chl a. Accessory pigments rather than chl a might be more strongly involved in the capacity of the algae to absorb light in deeper waters. On the other hand, the accumulation of chl a in plants growing in upper sublittoral zones might be associated with its higher absorption efficiency at higher irradiances compared to phycobilins, whose activity may become more rapidly light-saturated (Larkum & Weyrauch 1977).…”
Section: Changes In Chl a C And N Contentsmentioning
confidence: 99%